2009
DOI: 10.1021/jf9025019
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Enzyme-Linked Immunosorbent Assay (ELISA) for Quantification of Lysozyme in Cheese

Abstract: A competitive enzyme-linked immunosorbent assay (ELISA) was developed to quantify the amount of the preservative and potential allergen lysozyme in cheese using a commercially available monoclonal antibody against hen egg white lysozyme. The limit of detection for lysozyme in a cheese matrix amounted to 2.73 ng/mL, and the working range comprises 3.125-800 ng/mL. Intra- and interassay coefficients of variation were lower than 12%. Neither cross-reactivity with alpha-lactalbumin and human lysozyme nor unspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Peng et al reported a faradic impedance spectroscopy aptasensor using aptamer as recognition element for lysozyme analysis ). Schneider et al developed an enzyme-linked immunosorbent assay using antibody as recognition element (Schneider et al, 2010). However, the linear ranges of these methods were narrower than that of this article and recognition elements of these methods were low stability and high cost.…”
Section: Samplesmentioning
confidence: 85%
“…Peng et al reported a faradic impedance spectroscopy aptasensor using aptamer as recognition element for lysozyme analysis ). Schneider et al developed an enzyme-linked immunosorbent assay using antibody as recognition element (Schneider et al, 2010). However, the linear ranges of these methods were narrower than that of this article and recognition elements of these methods were low stability and high cost.…”
Section: Samplesmentioning
confidence: 85%
“…However, these methods require pre-treatment of the sample, expensive tools, qualified personnel and long-time analysis. The enzyme-linked immunosorbent assay (ELISA) is also used to this aim [32,35], but this approach has several disadvantages such as the nonspecific adsorption of substances generating false positives/negatives [36], the possible matrix effect on enzyme activity [37] and kit high cost. To overcome these problems, a multitude of sensors for lysozyme have been developed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, the use of lysozyme is widespread (Panari and Filippi, 2009); lysozyme has been detected in Grana Padano, in grated hard cheese mixtures (Cocolin et al, 2004;Iaconelli et al, 2008), and in semihard goat and ewe cheeses (Dragoni et al, 2011;Schneider et al, 2010bSchneider et al, , 2011. Even though the current commercial source for lysozyme is from HEW, it is present also in milk, blood serum, tears, and saliva (Callewaert and Michiels, 2010).…”
mentioning
confidence: 99%